The Influence Of Human Resource Competency And Accounting Information Systems On The Quality Of Village Financial Reports In Banda Aceh City At 2025 - Zulfikar Zulfikar; Irmawati Irmawati; Elviza Elviza (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to determine the influence of human resource competency and accounting information systems simultaneously on the quality of village financial reports in Banda Aceh City. The population in this study were Village Heads, Treasurers and Village Secretaries in Banda Aceh City with a total of 100 people, taken based on simple random sampling using the Slovin formula. This research method is quantitative, testing and analysis of primary data were carried out using statistical data processing application tools with multiple linear regression formulations. Based on the results of the research that has been done, it was found that Human Resource Competence and Accounting Information Systems have a significant influence on the Quality of Village Financial Reports in Banda Aceh City in 2025 simultaneously amounting to 59.995. Partially, Human Resource Competence has an influence of 3.603 while the Accounting Information System has an influence of 3.160.